Research Progress and Current Status of Metal Cutting Fluid Technology - LUO Xiuyu, XIAO Shaowen, ZHAN Wen, LI Yingpeng (Cailiao Baohu)
In recent years， with the rapid development of industries such as new energy vehicles， aerospace， and high-end equipment manufacturing， along with the integration of technologies like artificial intelligence and big data， machine tools are advancing toward higher levels of high-end，intelligent，and green technologies.Cutting fluids are essential for achieving efficient，precise，and low-cost metal cutting processes.However， with the rapid growth of the machinery manufacturing industry， the conflict between the low performance of traditional cutting fluids and the high-quality manufacturing requirements of core components has become increasingly evident.On the other hand， the green application and safe disposal of cutting fluids have become major obstacles to the green development of the industry.Therefore， addressing the series of issues associated with traditional cutting fluids is a critical research topic faced by both the machinery manufacturing industry and the environmental protection field.This paper took the limitations of traditional cutting fluids as the starting point， and organized the current research on cutting fluids from three dimensions: environmental protection， economy， and functionality.The latest research progress on lubrication and cooling mechanisms， process effects， and parameter optimization was reviewed， and the advantages and disadvantages of different cutting fluids， along with the issues encountered during their development， were analyzed.Finally， from the perspective of industrial practical applications， the paper provided an outlook on metal cutting fluids and offered theoretical insights and research directions for the functionalization and greenization of cutting fluid technology， aiming to promote the domestic substitution of cutting fluid technologies in China.